2023
DOI: 10.1038/s41467-023-42930-y
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin-facilitated invasion of BMI1-high hepatocellular carcinoma cells drives bile duct tumor thrombi formation

Lei-Bo Xu,
Yu-Fei Qin,
Liangping Su
et al.

Abstract: Bile duct tumor thrombosis (BDTT) is a complication mostly observed in patients with advanced hepatocellular carcinoma (HCC), causing jaundice and associated with poor clinical outcome. However, its underlying molecular mechanism is unclear. Here, we develop spontaneous preclinical HCC animal models with BDTT to identify the role of BMI1 expressing tumor initiating cells (BMI1high TICs) in inducing BDTT. BMI1 overexpression transforms liver progenitor cells into BMI1high TICs, which possess strong tumorigenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Recent studies have revealed the role of several cathepsins in promoting or inhibiting various cancers (e.g., lung (10), ovarian (11), thyroid (12), and colorectal (13)), including cathepsin B (CTSB) (14), cathepsin L (CTSL) (15), cathepsin G (CTSG) (16), and cathepsin S (CTSS) (17). However, few observational studies and clinical trials have investigated the relationship between cathepsins and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed the role of several cathepsins in promoting or inhibiting various cancers (e.g., lung (10), ovarian (11), thyroid (12), and colorectal (13)), including cathepsin B (CTSB) (14), cathepsin L (CTSL) (15), cathepsin G (CTSG) (16), and cathepsin S (CTSS) (17). However, few observational studies and clinical trials have investigated the relationship between cathepsins and cancer.…”
Section: Introductionmentioning
confidence: 99%